Platelet Function in Patients with Disseminated Intravascular Coagulation: Potential Markers for Improving DIC Diagnosis? - Petersen, Johanne Duus; Hvas, Christine Lodberg; Larsen, Julie Brogaard (Seminars in Thrombosis and Hemostasis, 2025)
Disseminated intravascular coagulation (DIC) is a severe complication often associated with critical illness. DIC is characterized by an uncontrolled systemic activation of the hemostatic system, leading to substantial consumption of platelets and coagulation factors. The diagnosis of DIC relies on a combination of clinical findings and laboratory results, yet DIC remains challenging to confirm, especially in early stages. This systematic review investigates the reported associations between platelet function and DIC and evaluates the potential of using platelet function markers as a supplement for DIC diagnosis. PubMed and Embase were searched for relevant literature. Human studies, which included patients with DIC and assessed platelet function using dynamic platelet function assays or soluble markers, were included. In total, 24 studies met the inclusion criteria. We found that DIC patients generally exhibit increased platelet activation in vivo, indicated by elevated plasma levels of soluble markers, while ex vivo platelet aggregation was consistently reduced compared to non-DIC patients and healthy controls; however, not all studies adjusted their results for platelet count. Soluble P-selectin was the most frequently studied plasma marker and was consistently increased in DIC patients; this was most pronounced when adjusted for platelet count. However, there was considerable heterogeneity between studies regarding both study design, patient populations, platelet function assessment, and DIC diagnosis, which complicates the comparison of findings across studies. Future studies accounting for low platelet counts in dynamic function tests are necessary to assess the role of platelet aggregation in relation to DIC.
Keywords: disseminated intravascular coagulation; platelet function; biomarker